"Postconcussive" Symptoms Explained by PTSD Symptom Severity in U.S. National Guard Personnel. (3rd April 2021) - Roberge, Erika M.; Baker, Shelby; Ely, Dillon; Bryan, AnnaBelle O.; Bryan, Craig J.; Rozek, David C.
Abstract: The aim of the present study was to evaluate the unique associations between self-report history of mild traumatic brain injury (mTBI) and posttraumatic stress disorder (PTSD) symptoms on functional outcomes years after head injury. National Guard personnel ( n  = 608) from the mountain west who denied history of head injury ( n  = 342, 56.3%) and with history of mTBI ( n  = 266, 43.7%) were included in the present analyses. Participants completed self-report study measures of emotional (i.e., depression, PTSD symptoms), social (i.e., relationship satisfaction and perceived social support), and other general (i.e., concentration difficulties and sleep disturbance) functioning through an online survey. PTSD symptoms explained unique variance in emotional, social, and general functioning above and beyond history of mTBI. After controlling for PTSD symptoms, mTBI was not associated with current depression symptoms, relationship satisfaction, social support, concentration, or sleep difficulties. Self-report of PTSD symptoms account for emotional, social, and general functioning impairments often attributed to mTBI and labeled postconcussive syndrome . Symptoms often described as postconcussive syndrome in patients with mild traumatic brain injury may be better explained from a psychological standpoint. Patients with history of mTBI and persistent complaints should be screened for mental health conditions. If mental health concerns are present, treatment of that disorder may be indicated.